1992
DOI: 10.1038/ki.1992.221
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of CD8 positive cells in nephrotoxic serum nephritis of WKY rats

Abstract: Following a small dose of nephrotoxic serum (NTS) WKY rats demonstrated crescentic glomerulonephritis, which was characterized by the early infiltration of CD8 positive cells in glomeruli. In vivo depletion of CD8 positive cells from WKY rats completely prevented proteinuria (4.6 +/- 4.8 mg/day vs. 105.3 +/- 11.6 mg/day on day 10; N = 19, P less than 0.001) and crescent formation (2.7 +/- 2.9% vs. 94.3 +/- 2.6%; P less than 0.001). Immunofluorescence revealed complete inhibition of the influx of CD8 positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
142
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 32 publications
1
142
1
Order By: Relevance
“…The cellular sources of CC chemokines in this model are unknown. MIP-1a, MIP-1b and RANTES are produced mainly by T lymphocytes [38], and numbers of CD8 þ cells increase in glomeruli in this model at early stages ( [36], our unpublished observation). Therefore, CD8 + cells might be responsible for the early induction of these chemokines in the model.…”
Section: Discussionmentioning
confidence: 65%
“…The cellular sources of CC chemokines in this model are unknown. MIP-1a, MIP-1b and RANTES are produced mainly by T lymphocytes [38], and numbers of CD8 þ cells increase in glomeruli in this model at early stages ( [36], our unpublished observation). Therefore, CD8 + cells might be responsible for the early induction of these chemokines in the model.…”
Section: Discussionmentioning
confidence: 65%
“…This may explain the finding that vIL-10 did not repress perforin, which is produced by CD8 + T cells. A previous study demonstrated that CD8 + T cells play an important role in experimental crescentic GN; 40 however, pCAGGS-vIL-10 gene transfer exhibited therapeutic effects without an apparent suppression of CD8 + T cells.…”
Section: Discussionmentioning
confidence: 90%
“…The peak influx of Mo/M occurs later (days 6 and 11) than that of CD8 ϩ cells (day 3). 35 In this study we investigated the role of MDC, a novel C-C chemokine for monocytes, activated lymphocytes, dendritic cells, and NK cells in the development of this model of GN. We first examined MDC expression in the glomeruli during the evolution of the lesion and then established its functional role with blocking Ab.…”
Section: Discussionmentioning
confidence: 99%
“…MDC riboprobe was synthesized with incorporation of 35 S-UTP as previously described. 10 Following in situ hybridization and before dehydration, the slides were incubated for 5 minutes in Tris-buffered saline.…”
Section: In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation